2012
DOI: 10.1177/0731684412437987
|View full text |Cite
|
Sign up to set email alerts
|

Flexural and impact properties of flax woven, knitted and sequentially stacked knitted/woven preform reinforced epoxy composites

Abstract: In this article, plain woven, rib knitted and sequentially stacked rib knitted/plain woven, flax fabric reinforced epoxy composites are investigated for their flexural and impact properties. The effect of lay-up angle and the number of preform layers on the above-mentioned properties are also studied. The composite laminates were processed by hand lay-up technique using 2 and 4 mm thick spacers and cured under pressure of 3 bar for 2 h at 50 C, followed by curing in an oven at 120 C for 1 h. Specimen preparati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…The sample with a fiber orientation of 0° showed the maximum impact strength. The epoxy laminates reinforced with woven flax preforms performed better in impact than sequentially arranged knitted/woven preforms . The samples made through injection molding showed lower impact resistance (about 150% for a given fiber volume fraction) than compression molded samples .…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The sample with a fiber orientation of 0° showed the maximum impact strength. The epoxy laminates reinforced with woven flax preforms performed better in impact than sequentially arranged knitted/woven preforms . The samples made through injection molding showed lower impact resistance (about 150% for a given fiber volume fraction) than compression molded samples .…”
Section: Introductionmentioning
confidence: 90%
“…Many researchers have studied the impact behavior of natural fiber composites. The characterization, in terms of impact strength, is predominantly carried out under in‐plane impact load using Charpy and Izod impact testers. For example, previous studies reported that the Charpy impact strengths of nonwoven hemp fiber/PP, flax yarn/polylactic acid (PLA), flax fiber mat/PP, and short latania fiber/(PP/ethylene‐propylene‐diene‐monomer) composites, respectively, increase with increasing fiber content, while a decreasing trend in impact strength was observed with increasing fiber content in the case of short fibers (lyocell, hemp, and jute) reinforced polyhydroxybutyrate composites.…”
Section: Introductionmentioning
confidence: 99%
“…The findings from Haller et al (2006) proved that knitted textiles show high potential for reinforcement in engineering applications, particularly as results proved that maximum load tripled and stiffness strength doubled when the wood was reinforced with the biaxial knit structure. Muralidhar et al (2012) characterised the flexural and impact behaviour of textile composites made from laminates of knitted and woven preforms stacked together. The Plate 4.…”
Section: Textile Technologiesmentioning
confidence: 99%
“…Padaki and Sugun reviewed various applications of knitted woven fabric composites and concluded that knitted fabric performs well compared with woven fabric composite due to low resistance to deformation, minimum material wastage and cost. Muralidhar et al compared the flexural properties of plain woven and knitted fabric composites and found that composite with knitted woven fabric in the outer layer gives better mechanical properties. Hu et al also observed the same and found that 3D stitched woven‐knitted basalt composite increases Young's modulus of the composite material.…”
Section: Introductionmentioning
confidence: 99%